Fast times at Ridgemont High [videorecording (DVD)] - Heckerling, Amy; Penn, Sean, 1960-; Leigh, Jennifer Jason, 1962-; Reinhold, Judge, 1957-; Crowe, Cameron, 1957- (Universal, 2004)
A comedy that chronicles the trials and tribulations of several high school students.